Extravagancias organológicas: una revisión de la iconografía musical en el arte latinoamericano contemporáneo (2015)
Musical iconography is considered a discipline that arises as an alternative of descriptive and explanatory analysis of the musical elements that appear in the plastic arts. Through the evaluation of the images, the researcher obtained data that contribute to the knowledge of the organizational aspects, the execution of the instruments and the vocal performance, the portraits, the scenographies, the constitution of the musical groups, the context and other elements that allow to contribute to the history of music. Therefore, in the mid-twentieth century it was established as a study methodology, primarily in favor of musicology. In this article we propose a brief review of some cases of contemporary Latin American art, in which we can observe that, despite the deformity of the musical elements, suggested by the innovative and avant-garde styles of the twentieth and twenty-first centuries, they are the visual arts A source for musicological data collection.